Numerical simulation and safety evaluation of multi-source leakage of buried product oil pipeline. Issue 3 (14th September 2022) - Zhang, Baozhen; Kang, Rongxue; Zhu, Hongqing; Yuan, Qi; Zhang, Qing; Zhou, Ximeng
ABSTRACT: The leakage from a buried oil pipeline has the potential to inflict great economic losses and environmental pollution owing to the long-term and concealment. Therefore, studying the diffusion law and safety evaluation of buried product oil pipeline leakage is critical. In this study, the single-hole and double-hole leakage of buried diesel pipeline are used as examples, and the variation laws of inlet and outlet pressure, flow velocity, flow rate and diffusion range of buried product oil leakage is studied by means of computational fluid dynamics (CFD) method. Then, the risk of multi-source leakage of buried product pipeline is evaluated by analytic hierarchy process (AHP) and fuzzy synthetic evaluation (FSE). The results show that the product oil leakage diffusion in front of the orifice is similar to a jet phenomenon, and the diffusion velocity decreases with the increase of the distance. The maximum flow velocity and stable flow velocity of single-hole leakage are higher than those of double-hole leakage. The flow velocity of the single-hole leakage is stable at 28 m/s and that of the double-hole leakage is 16 m/s and 14 m/s and fluctuates in a small range. When the pipeline leaks, the inlet and outlet pressures change, and the inlet pressure changes 1.6 1.8 times the outlet pressure. Moreover, the oil leakage from the single and double holes achieved a stable level after 0.4s, and the difference was only 0.008 m 3 /s. At the initial stage of leakage, the longitudinal diffusion range of double-hole leakage is larger than that of single-hole leakage, but the gap is getting smaller with time, while the vertical diffusion is similar, and the leaked oil reaches the ground almost simultaneously. Finally, the synthetic evaluation of leakage accident risk probability is 81.3%, and the risk level is 'high.'